Linguistic Dimensions of Subtitling. Perspectives from Taiwan - Chen, Sheng-Jie (Meta, 2004)
AbstractThis study investigates the linguistic dimensions of the subtitling of English movies into Chinese. The data derive from literature analysis, interviews with experienced subtitlers and administrators of translation agencies, my self-analysis as an experienced subtitler, and an analysis of four English movies rendered into Chinese subtitles. Grounded research methods are used to analyze the data and complete the report. The results indicate that several factors affect the quality of subtitling, including movie pirating, uncontrollable outsourced projects, economic factors, and linguistic factors. In the Chinese subtitles, swearwords are toned down, some punctuation marks and inessential information are omitted, and despite the source-language register, literary Chinese is used for brevity.